Sero-Prevalence Of HIV Antibody Amongst Std Clinic Attenders In Calcutta - Neogi D.K; Roy Alok Kumar; Chakraborti Tapasri; Dutta Pijush Kanti (Wolters Kluwer Medknow Publications, 1999)
Total one thousand one hundred fifty sexually transmitted disease (STD) clinic attendees from different medical colleges and hospitals of Calcutta were examined for HIV antibodies first with ELISA and if positive, were confirmed by western blot. In the first phase, which constituted of four hundred cases from march â€97 to April â€97, 2.25% cases showed seropositivity. The second phase which consisted of five hundred cases between September â€97 to October â€97, 2.4% cases showed seropositivity. The third phase which consisted of two hundred fifty cases between February â€98 and March â€98, 3.2% of cases showed seropositivity. Thus, a slowly but steadily increasing rate of seropositivity to HIV was noted.